2012
DOI: 10.1186/1471-2229-12-224
|View full text |Cite
|
Sign up to set email alerts
|

Auxin as a player in the biocontrol of Fusarium head blight disease of barley and its potential as a disease control agent

Abstract: BackgroundMechanisms involved in the biological control of plant diseases are varied and complex. Hormones, including the auxin indole acetic acid (IAA) and abscisic acid (ABA), are essential regulators of a multitude of biological functions, including plant responses to biotic and abiotic stressors. This study set out to determine what hormones might play a role in Pseudomonas fluorescens –mediated control of Fusarium head blight (FHB) disease of barley and to determine if biocontrol-associated hormones direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 57 publications
1
55
0
3
Order By: Relevance
“…Similarly, infection with e.g. Fusarium species (Fernández-Falcón et al, 2003;Petti et al, 2012), Magnaporthe grisea (Ueno et al, 2004) and Botrytis sp. (Yu et al, 2008) could also be controlled by application of IAA.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, infection with e.g. Fusarium species (Fernández-Falcón et al, 2003;Petti et al, 2012), Magnaporthe grisea (Ueno et al, 2004) and Botrytis sp. (Yu et al, 2008) could also be controlled by application of IAA.…”
Section: Discussionmentioning
confidence: 98%
“…Pseudomonas fluoresecens yang diinokulasikan pada gandum memacu terbentuknya IAA pada pucuk tanaman sehingga menekan gejala dan kehilangan hasil akibat penyakit hawar pucuk Fusarium (Petti et al 2012); tetapi hal tersebut tidak berlaku untuk hormon ABA (Mejia et al 2008). Mekanisme penekanan patogen yang ditemukan pada tanaman kakao oleh endofit Trichoderma umumnya kompetisi untuk substrat atau ruang (Hakkar et al 2014).…”
Section: Uji Tantang Dengan Phytophthoraunclassified
“…This weak inhibition response is in agreement with the results of Alam et al [19] who reported that both IAA and BAP led to a weak inhibition (4 and 11%; respectively) to the mycelium growth of anthracnose fungal pathogen (Colletotrichum spp.). Petti et al [49] reported that IAA has no effect on F. culmorum growth when using a nutrient-rich medium.…”
Section: Discussionmentioning
confidence: 99%